MAIN GOALS OF PRODUCTION OF THE MAIN TYPES OF LIVESTOCK PRODUCTS IN THE REGIONS AND MECHANISMS FOR ITS IMPLEMENTATION - Khasanova , Dildora (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This thesis provides a comprehensive analysis of the main goals of livestock production and the mechanisms for their implementation based on economic and statistical methods. The current mechanisms for increasing the efficiency of livestock production in the regions are studied, and proposals and recommendations for their improvement are developed.